2010
DOI: 10.1007/s11104-009-0266-9
|View full text |Cite
|
Sign up to set email alerts
|

Release of plant-borne flavonoids into the rhizosphere and their role in plant nutrition

Abstract: Plants release a multitude of organic compounds into the rhizosphere, some of which are flavonoids. These products of secondary metabolism are mainly studied for their antioxidant properties and for their role in the establishment of rhizobium-legume symbiosis; however, it has been recently demonstrated that flavonoids can also affect nutrient availability through soil chemical changes. This review will give an overview of the types and amounts of flavonoids released by roots of different plant species, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
232
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(241 citation statements)
references
References 130 publications
7
232
0
2
Order By: Relevance
“…An analogous process has been described for flavonoids and citrate released by roots of white lupin, which, solubilizing Fe from an insoluble Fe phosphate, favored indirectly the mobilization and the availability of phosphate (Shaw et al 2006;Tomasi et al 2008). With respect to Fe, it has been demonstrated that the Fe-mobilization capacity of these organic ligands (Cesco et al 2000(Cesco et al , 2010 and the contribution of their Fe complexes in the acquisition process of the micronutrient by plants (Cesco et al 2002(Cesco et al , 2006Pinton et al 1999;Tomasi et al 2009a, b) could be quite different among the complexes. In the mobilization process, MS s can act alone or in combination with simple carboxylic acids and organic reducing agents of different origin; in this combined form, an additive effect with an enhanced extent of Fe dissolution from minerals has been observed (Dhungana et al 2007;Dehner et al 2010).…”
Section: Fe Complexation Processesmentioning
confidence: 80%
See 1 more Smart Citation
“…An analogous process has been described for flavonoids and citrate released by roots of white lupin, which, solubilizing Fe from an insoluble Fe phosphate, favored indirectly the mobilization and the availability of phosphate (Shaw et al 2006;Tomasi et al 2008). With respect to Fe, it has been demonstrated that the Fe-mobilization capacity of these organic ligands (Cesco et al 2000(Cesco et al , 2010 and the contribution of their Fe complexes in the acquisition process of the micronutrient by plants (Cesco et al 2002(Cesco et al , 2006Pinton et al 1999;Tomasi et al 2009a, b) could be quite different among the complexes. In the mobilization process, MS s can act alone or in combination with simple carboxylic acids and organic reducing agents of different origin; in this combined form, an additive effect with an enhanced extent of Fe dissolution from minerals has been observed (Dhungana et al 2007;Dehner et al 2010).…”
Section: Fe Complexation Processesmentioning
confidence: 80%
“…Flavonoids released by roots have a direct effect on soil minerals and on biological activity in the soil that play an important role in Fe solubilization processes (El Hajji et al 2006;Tomasi et al 2008;Cesco et al 2012). However, although the impact of flavonoids on soil microorganisms could also be of relevance in terms of microbe-mediated Fe oxidation-reduction in soil (Tomasi et al 2008;Cesco et al 2010Cesco et al , 2012, the relative contribution of these molecules to the Fe availability in the rhizosphere and to the use of this Fe source for plant nutrient acquisition has not yet been comprehensively studied. It appears evident that the release of Fe III -complexing organic compounds by roots and microorganisms can contribute to Fe (hydr)oxides dissolution and/or to Fe mobilization from unavailable sources (see Figs.…”
Section: Fe Complexation Processesmentioning
confidence: 99%
“…4G). Naringenin is widespread in legumes and nonlegumes (28), which probably explains why transfer is enhanced in the rhizosphere of several nonhost plants, and largely involved in communication with plant-associated bacteria. In addition to its crucial role in the nodulation process, it was shown to stimulate wheat and Arabidopsis thaliana colonization by A. caulinodans (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the JFW16-induced rhizospheric acidification increased Fe availability, and further alleviated adverse impacts imposed by alkaline pH conditions. Interestingly, Strategy I plants can produce and exudate several secondary metabolites such as phenolics, flavonoids and flavins to increase Fe availability in the rhizosphere and in the root apoplast (Jin et al 2007;Cesco et al 2010;Rodríguez-Celma et al 2011). Red clover (Trifolium pratense) increases the utilization of cell wall Fe pools under Fe-deficient conditions by the release of phenolics into root vicinity (Jin et al 2007).…”
Section: Accumulated In Rootsmentioning
confidence: 99%